(untitled) (Mustansiria Dental Journal, 2024)
Aim of the study: The purpose of the present investigation was to see how efficient silver diamine fluoride (SDF) solution treatment to prevent dental root caries. Materials and method: This research was done at Iraq’s geriatric facilities. Forty seniors with active caries lesions were fortuitously assigned into two groups: Group 1 (placebo control)—doubles Twice-Annual treatment with soda water; Group 2—Doubles Twice-Annual treatment with silver diamine fluoride solution. Results: After 18 months, the arrest rates of root caries were 28 percent in group1 (control) and 88 percent group 2 silver diamine fluoride solutions (x2 test, p < 0.05). There was a considerable relation (dependent) between silver diamine fluoride and stopping root surface dental caries Chi=7.08, df=2, P<0.05, which means that silver diamine fluoride was efficient in stopping dental caries while there was no relation (independent) between placebo dye and arresting caries, Chi=1.33 df=2 P>0.05. Conclusions: Silver diamine fluoride solution was helpful in avoiding root caries in elderly people who do not have access to fluoridated water.